Giant Microwave Spontaneous Emission Enhancements in Planar Aperture Waveguide Structures. Issue 6 (28th April 2021) - Shugayev, Roman; Devkota, Jagannath; Crawford, Scott; Lu, Ping; Buric, Michael
Abstract: Microwave interactions are an invaluable tool for probing atomic states of matter and are currently being extensively explored for the development of scalable quantum computing. However, many of the available methods for spectroscopic analysis and photonic quantum manipulations are inaccessible for microwaves due to the weak spontaneous emission of quantum emitters. In this work, a mechanism for giant resonant enhancement of spontaneous emission from magnetic dipole emitters is suggested that employs a new phenomenon of near field impedance cancellation via magnetic flux confinement. Enhancements of at least 10 11 are theoretically shown for structures with 100 nm features, and much greater potential enhancements are predicted with this method. Subsequently, the realization of integrated systems with enhanced quantum emitters using microwave spoof plasmon waveguides is demonstrated. Taken together, these findings will pave the way for microwave quantum photonics and microwave hybrid quantum computing. Abstract : Many applied and basic science phenomena rely on efficient spontaneous emission. In this work, new class of electromagnetic resonance termed near field impedance cancellation is proposed. Using this effect, the possibility of giant spontaneous emission enhancements in planar aperture structures is shown. These results set new performance limits for quantum emitters and open doors for novel photonic applications at microwaves.